The process of lesson study as a strategy for the development of teaching in primary schools : a case study in the Western Cape Province, South Africa - Coe, Karen Lee (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Curriculum Studies))--University of Stellenbosch, 2010.